Diabetes, smoking, family hypertension and consultations number, could be risk factors for preeclampsia in pregnant women in the region Nouakchott in Mauritania? - MARIEM SIDI MOHAMED; SETTY SASS; AHMED ZEIN; AHMED LBARAE; ABDERRAZZAK KHADMAOUI; L. AICHA LRHORFI; KHALLAYOUN SOAD; RACHID BENGUEDDOUR (International Journal of Pharma and Bio Sciences, 2018)
Preeclampsia is a major public health problem in pregnant women. The objective of our study is to identify the risk factors for preeclampsia in pregnant women. Thereby, we conducted a prospective study in the maternity ward of the CHEIKH ZAYED Hospital Center in Nouakchott, during the period from 2015 to 2016.Otherwise,360 pregnant womenwere interviewed, of which 31% (n = 112) had complications of high blood pressure. In addition, 50 of these hypertensive women were preeclamptic, of whom46% aged between years 20 and 30, 52% are Black Moors, and 82% had no fixed occupation. Preeclamptic multi-gestures represented more than half of cases (62%), nearly half of cases 48% had a family antecedent and the majority (84%) had consulted persistently (> 4).Nevertheless, the impact results were much more alarming, which called for adequate and effective intervention to deal with this scourge.